2019
DOI: 10.3171/2017.10.jns17779
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic endonasal transoculomotor triangle approach for adenomas invading the parapeduncular space: surgical anatomy, technical nuances, and case series

Abstract: OBJECTIVEPituitary adenomas may extend into the parapeduncular space by invading through the roof of the cavernous sinus. Currently, a transcranial approach is the preferred choice, with or without the combination of an endonasal approach. In this paper the authors present a novel surgical approach that takes advantage of the natural corridor provided by the tumor to further open the oculomotor triangle and resect tumor extension into the parapeduncular space. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Since the long‐term surgical remission rate is highly dependent on cavernous sinus invasion and the extent of resection, 16,20 proactive surgery with an intent to cure should be planned to achieve local control and endocrinological remission, especially for SG tumours. Encouragingly, in recent years, transsphenoidal surgery has shown good results in treating pituitary adenomas with a high Knosp grade and cavernous sinus invasion 5‐11,21 . Despite refinement in surgical and monitoring techniques, operative risk from radical resection should still be kept in mind during the surgical plan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the long‐term surgical remission rate is highly dependent on cavernous sinus invasion and the extent of resection, 16,20 proactive surgery with an intent to cure should be planned to achieve local control and endocrinological remission, especially for SG tumours. Encouragingly, in recent years, transsphenoidal surgery has shown good results in treating pituitary adenomas with a high Knosp grade and cavernous sinus invasion 5‐11,21 . Despite refinement in surgical and monitoring techniques, operative risk from radical resection should still be kept in mind during the surgical plan.…”
Section: Discussionmentioning
confidence: 99%
“…The favoured corridor for tumour resection is via the transsphenoidal route, using either a microscope or an endoscope. With advances in extended endonasal surgery, pituitary tumours invading the cavernous sinus could be directly removed by opening the medial, anterior, inferior walls of the cavernous sinus and different compartments inside it 5‐11 . Even the medial wall of the cavernous sinus invaded by the tumour could be removed with a microsurgical technique under endoscopy 5,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Kawase et al found three weak points of CS: at the level of venous plexus of SOF, at the medial wall of pituitary gland, and at the cisternal segment of the intracavernous portion of IIIrd and Vth cranial nerves [48]. According to some authors, macro-PAs may indeed show a preferential growth pathway extending into the parapeduncular space through the oculomotor triangle [49][50][51][52]. The dural layer of the cistern of the oculomotor nerve could be thin or even lacking, representing a possible point of diffusion exploitable by PAs [49].…”
Section: Anatomy Of the Sellar And Parasellar Regionmentioning
confidence: 99%
“…For example, when the tumor breaks through the superior triangle and enters the parapeduncular space, the trajectory of the posterior communicating artery runs medial and nearly parallel to the oculomotor nerve in most cases. 5 When the tumor breaks through the posterior triangle, the superior cerebellar artery and other basilar artery branches will be encountered. An awareness of intracavernous and intracranial neurovascular structure relationships involved in tumor invasion can potentially prevent vascular injuries.…”
Section: Discussionmentioning
confidence: 99%